Ministering to the Ministers: The Discipline of Recalcitrant Clergy in the Diocese of Lincoln 1830–1845 - Knight, Frances (Studies in church history, 1989)
By 1830, the effectiveness of the Church of England’s ministry was believed to have become seriously compromised, because it still possessed no adequate means for disciplining its clergy. It had long been recognized that the Church’s structure, and in particular the strength of the parson’s freehold, made it impossible for it to exercise the same sort of authority over its ministers as the dissenting bodies, or even the Church of Scotland. The view that the inadequacy of disciplinary measures was detrimental to the standing of the Established Church was in fact shared both by those hostile to and those supportive of it. On the one hand, John Wade’s Extraordinary Black Book, published in 1831 and intended as an indictment of corruption, rapacity, and jobbery within the Establishment, made the exposure of abuses in Church discipline one of its principal objectives. Not unnaturally, loyal churchmen also expressed considerable anxiety at the spectacle of bishops almost powerless in the face of clerical malefactors within their dioceses. Throughout the 1830s, the correspondence of clergy and the speeches of senior Anglicans in Parliament reflect an urgent desire that appropriate measures be swiftly introduced in order to combat cases of clerical irregularity.